(untitled) (Indo-MathEdu Intellectuals Journal, 2024)
In the digital era, where the development of science and technology is increasingly modern, society is faced with various kinds of moral and ethical crises due to the sophistication of the world and technological developments. This technological development also affects the morality of the younger generation and causes major changes in the behavior and social interaction of today’s young generation. This research uses a qualitative method. A qualitative approach is used in content analysis as a research technique, especially in collecting data from various literature sources. Content analysis is used as a model to investigate data in the form of images, text, symbols, and the like. The results of the analysis show that the emphasis on moral and ethical education integrated in Pancasila shows the importance of forming responsible character and helping the younger generation in developing empathy and compassion for others. Therefore, a deep understanding of Pancasila as an ethos, ideology, and tool of self-defense is crucial in responding to the impact of the current era of globalization that continues to develop